The Sound of ”Quaternary” - Jef Vandenberghe (Quaternary, 2020)
It is useful to re-consider at specific times the strategy of a journal. Some thoughts are expressed here at the occasion of the renewal of the editorship of ”Quaternary”. No changes are envisaged in the multidisciplinary character of the journal. In addition, it is felt necessary to increasingly attract the creative input from underrepresented researchers in Quaternary science (e.g., young scientists, female scientists, scientists from weakly developed countries).